If and when social and economic leader-member exchange relationships predict follower work effort. Issue 8 (28th October 2014) - Buch, Robert; Kuvaas, Bård; Dysvik, Anders; Schyns, Birgit
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to conceptualize social leader-member exchange (SLMX) and economic leader-member exchange (ELMX) as two separate dimensions of leader-member exchange, and examines how intrinsic work motivation moderates their relationship with follower work effort. Design/methodology/approach – Data were obtained from 352 employee-leader dyads from the public health sector in Norway (response rate=61.9 percent). Hierarchical linear modeling was used to test the relationship between subordinate rated SLMX and ELMX relationships and leader ratings of work effort. Findings – This study replicates prior research showing that SLMX is positively related and ELMX negatively related to followers' work effort. A significant interaction between SLMX and intrinsic motivation is also revealed, suggesting that SLMX relationships are important with respect to work effort for followers who exhibit lower levels of intrinsic work motivation. Research limitations/implications – The data were cross-sectional, thus prohibiting causal inferences. Practical implications – SLMX relationships may be particularly important for the work effort of followers low in intrinsic motivation. Leaders may draw on this finding and seek to aid the development of the relationship by means of relationship-oriented behaviors. Originality/value – Given the importance of maximizing the performance of all the followers, a better understanding of the conditions under which SLMX and ELMX relationships relate to work effort is particularly important. The present study advances knowledge on SLMX and ELMX relationships by demonstrating how intrinsic motivation moderates how SLMX and ELMX relationships relate to follower work effort.